Beginning algebra. - Baratto, Stefan; Bergman, Barry; Hutchison, Donald, 1948- (New York, NY : McGraw-Hill Science/Engineering/Math, 2013)
'Letter from the Authors Dear Colleagues, We believe the key to learning mathematics, at any level, is active participation! We have revised our textbook series to specifically emphasize GROWING MATH SKILLS through active learning. Students who are active participants in the learning process have a greater opportunity to construct their own mathematical ideas and make stronger connections to concepts covered in their course. This participation leads to better understanding, retention, success, and confidence. In order to grow student math skills, we have integrated features throughout our textbook series that reflect our philosophy. Specifically, our chapter-opening vignettes and an array of section exercises relate to a singular topic or theme to engage students while identifying the relevance of mathematics. The Check Yourself exercises, which include optional calculator references, are designed to keep students actively engaged in the learning process. Our exercise sets include application problems'--
Includes index.
Keywords: Algebra -- Textbooks